I2C Sensors System for PLC Using Microcontroller - Angga Dewanta, Alexander Rahma; Suwarno, Djoko Untoro (SENATIK STT Adisutjipto, 2018)
In general, PLCs has digital inputs and outputs system. The PLC additional system for analog input on the PLC is limited to sensor output in the form of a voltage of 1-5V (or 4mA to 20mA current). The development of I2C-based sensor technology is not suitable for PLCs. In this research, an I2C-based sensors system was designed and made that can be connected to the PLC. Data from the I2C sensor is sent to the DM memory in the PLC via RS232 serial communication. The sensor used was an LDR as a light sensor and a BMP180 sensor to measure atmospheric pressure and room temperature. From the experiment, the results of the LDR sensor were 100% successful and the data transmission from the BMP180 sensor was well recognized in the PLC